Experimental Constraints on Forecasting the Location of Volcanic Eruptions from Pre-eruptive Surface Deformation - Guldstrand, Frank; Galland, Olivier; Hallot, Erwan; Burchardt, Steffi (Frontiers in Earth Science, 2018)
Volcanic eruptions pose a threat to lives and property when volcano flanks and surroundings are densely populated. The local impact of an eruption depends firstly on its location, whether it occurs near a volcano summit, or down on the flanks. Then forecasting, with a defined accuracy, the location of a potential, imminent eruption would significantly improve the assessment and mitigation of volcanic hazards. Currently, the conventional volcano monitoring methods based on the analysis of surface deformation assesses whether a volcano may erupt but are not implemented to locate imminent eruptions in real time. Here we show how surface deformation induced by ascending eruptive feeders can be used to forecast the eruption location through a simple geometrical analysis. Our analysis builds on the results of 33 scaled laboratory experiments simulating the emplacement of viscous magma intrusions in a brittle, cohesive Coulomb crust under lithostatic stress conditions. The intrusion-induced surface deformation was systematically monitored at high spatial and temporal resolution. In all the experiments, surface deformation preceding the eruptions resulted in systematic uplift, regardless of the intrusion shape. The analysis of the surface deformation patterns leads to the definition of a vector between the center of the uplifted area and the point of maximum uplift, which systematically acted as a precursor to the eruption's location. The temporal evolution of this vector indicated the direction in which the subsequent eruption would occur and ultimately the location itself, irrespective of the feeder shapes. Our findings represent a new approach on how surface deformation on active volcanoes that are not in active rifts could be analysed and used prior to an eruption with a real potential to improve hazard mitigation.